1979
DOI: 10.1007/bf00401005
|View full text |Cite
|
Sign up to set email alerts
|

Lipogenesis in Ehrlich ascites tumor cells under anaerobic culture conditions

Abstract: Anaerobic culture conditions (95% argon/5% CO2) caused a slightly greater increase in total lipids of Ehrlich ascites tumor cells than a gas phase of 20% O2, 75% N2, 5% CO2. Whereas the rate of [U-14C]acetate incorporation into total lipids and lipid-subclasses rose markedly in the absence of oxygen, a drastic decrease of [U-14C]pyruvate and [1-14C]octanoate incorporation as well as a 30% reduction of 3H incorporation into lipids from tritiated water were observed under these conditions. Since profound changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

1985
1985
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…C]acetate incorporated into lipids is increased in Ehrlich ascites tumor cells[31]. Similarly, this study showed that [1-14 C]acetate incorporation into the lipid-soluble fraction tended to be enhanced in tumor cells under hypoxia.…”
supporting
confidence: 71%
“…C]acetate incorporated into lipids is increased in Ehrlich ascites tumor cells[31]. Similarly, this study showed that [1-14 C]acetate incorporation into the lipid-soluble fraction tended to be enhanced in tumor cells under hypoxia.…”
supporting
confidence: 71%
“…The incorporation of acetate into fatty acids has been investigated by radiolabeling methods. The results indicated that the incorporation of radiolabeled acetate into fatty acid increased under hypoxia in different cancer lines [45,46]. The increase of fatty acid synthesis is correlated with the activated expression of fatty acid synthetase (FAS) in tumor cells under hypoxic conditions [47,48].…”
Section: Resultsmentioning
confidence: 99%